Galois Groups over ℚ: proceedings of a Workshop held March 23-27, 1987 - Ihara, Yasutaka; Ribet, K.; Serre, Jean-Pierre (Mathematical Sciences Research Institute Publications, 1989)
This volume is being published in connection with a March, 1987 workshop on Galois groups over Q and related topics, held at the Mathematical Sciences Research Institute in Berkeley. The organizing committee for the workshop consisted of Kenneth Ribet (chairman), Yasutaka Ihara, and Jean-Pierre Serre. The volume contains key original papers by experts in the field, and treats a variety of questions in arithmetical algebraic geometry. A number of the contributions discuss Galois actions on fundamental groups, and associated topics: these include Fermat curves, Gauss sums, cyclotomic units, and motivic questions. Other themes which reoccur include semistable reduction of algebraic varieties, deformations of Galois representations, and connections between Galois representations and modular forms. The authors contributing to the volume are: G.W. Anderson, D. Blasius, D. Ramakrishnan, P. Deligne, Y. Ihara, U. Jannsen, B.H. Matzat, B. Maszur, and K. Wingberg. The contributions are of exceptionally high quality, and this book will have permanent value. The volume will be of great interest to students and established workers in many areas of algebraic number theory and algebraic geometry